Detection of extended spectrum β-lactamase among gram negative clinical isolates from a tertiary care hospital in South India - K, Balan (International Journal of Research in Medical Sciences, 2017)
Background: The β lactamase enzymes produced by the organisms break down the structural beta-lactam ring of β lactam antibiotics. Many genera of gram negative bacteria possess a naturally occurring, chromosomally mediated β lactamase and also some are plasmid mediated β lactamases. The objective of the study was to detect extended spectrum β lactamases among gram negative clinical isolates. Methods: 200 clinical were subjected to routine disc diffusion technique and zone diameter of ≤27mm for Cefotaxime and ≤22mm for Ceftazidime or ≤25mm for Ceftriaxone were included in this study. The strains are subjected to double disc synergy test. Results: Of 200 samples, 174 yielded organisms belonging to enterobacteriaceae and 26 yielded growth of nonfermenters. Out of 174 members of enterobacteriaceae family, 122 were E. coli, 36 Klebsiella spp, 8 Proteus spp, 5 Enterobacter spp and 3 Citrobacter spp. Out of 26 nonfermenters, 18 were Pseudomonas spp and 8 were Acinetobacter. Conclusions: In the present study prevalence of ESBL was 23.3%, the high prevalence may be due to irrational use of third generation cephalosporins in both the hospital and community.